Jazz religion, the second line, and black New Orleans - Turner, Richard Brent (Indiana Univ. Press, 2009)
Introduction : Follow the second line -- The Haiti-New Orleans vodou connection : Zora Neale Hurston as initiate observer -- Mardi Gras Indians and second lines, sequin artists and rara bands : street festivals and performances in New Orleans and Haiti -- Interlude: The healing arts of African diasporic religion -- In rhythm with the spirit : New Orleans jazz funerals and the African diaspora -- Epilogue : A jazz funeral for "a city that care forgot" : the New Orleans diaspora after Hurricane Katrina